Strategic Clarity and its Impact on Improving the Mental Image of the Organization: Analytical Research at the University of Fallujah - Awad Mahdi*, Uday; Hassoon Al-Taie, Ali (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research emphasizes the need for the organization to redistribute powers and responsibilities internally, empower its human resources, and grant it various powers to present the opinions and proposals necessary to achieve this. Theoretical Framework: According to researchers (Ritchie-Dunham & Puente, 2008), the organization needs to establish its roots in its surrounding environment, it needs to strengthen its mental image and recognize the role that strategic clarity plays in achieving this. Design/Methodology/Approach: Analysis of study data in three colleges (2023-2024), using strategic clarity in its components (clarity of goals, clarity of organizational structure, clarity of employees’ role, clarity of use of resources, clarity of procedures and activities), mental image in its components (cognitive component, behavioural component, and emotional component). Findings: The results highlight a statistically significant relationship between strategic clarity and the organization’s mental image in the research field. Research Implications: The results confirm that strategic clarity plays an important role in enhancing the mental image of the organization, by enhancing the cognitive and behavioural components of the human resources it deals with and enhancing its emotional state within society. Originality/Value: This study prepares a guide on the nature of the procedures and activities required of its employees and the steps that must be adhered to to achieve the desired results, with the necessity of employing legal and ethical principles to ensure the enhancement of knowledge and experience among its employees.